Weblogs: Critical Factors Affecting Knowledge-Sharing Among Bloggers - Tan, Christine Nya Ling; Ng, Tuan Hock; LiM, Ying San (Journal of Knowledge Management Practice, 2012)
Weblogs or commonly known as blogs allows various opportunities for bloggers to easily share knowledge through their experiences, thoughts, and feelings. The intention of this paper is to understand and examine the factors that affect knowledgesharing (KS) in blogs. Five (5) of factors identified as crucial in this study are: knowledge self-efficacy; personal outcome expectations; subjective norms; feedback; ICT (Information and Communication Technology) usage. The findings obtained are based on the 250 questionnaires distributed and collected from bloggers by means of convenience sampling. Based on the results, it is established that knowledge self-efficacy, personal outcome expectations, subjective norms, feedback, and ICT usage significantly influence KS among bloggers. This study justifies the need to improve both the individual and technological aspects of blogging so as to further increase the likelihood and tendency of bloggers to share their knowledge and opinions interactively on multiple topics and issues through this alternative mainstream media known as blogs.